Creative employee desired? Recruiters’ expectations and the climate for creativity - Szynkowski, Jędrzej (Creativity in Business Practice. Part 2, 2019)
According to the latest forecasts regarding the dynamics of changes in the labour market, in the coming years, creativity and related skills will play a key role in organizational development. The chapter briefly presents the main challenges faced by the employees of recruitment departments and the people managing creativity in companies. Reference was made to the results of research in the field of work psychology, creativity and organization, including Goran Ekvall concept of creativity.